Early migration predicts aseptic loosening of cementless femoral stems: a long-term study - Streit, Marcus R.; Häussler, Daniel; Bruckner, Thomas; Proctor, Tanja; Innmann, Moritz Maximilian; Merle, Christian; Gotterbarm, Tobias; Weiss, Stefan (Clinical orthopaedics and related research, 2016)
Excessive early migration of cemented stems and cups after THA has been associated with poor long-term survival and allows predictable evaluation of implant performance. However, there are few data regarding the relationship between early migration and aseptic loosening of cementless femoral components, and whether early migration might predict late failure has not been evaluated, to our knowledge. Einzel-Bild-Röntgen-Analyse-femoral component analysis (EBRA-FCA) is a validated technique to accurately measure axial femoral stem migration without the need for tantalum markers, can be performed retrospectively, and may be a suitable tool to identify poor performing implants before their widespread use. - Questions/purposes. We asked: (1) Is axial migration within the first 24 months as assessed by EBRA-FCA greater among cementless stems that develop aseptic loosening than those that remain well fixed through the second decade; (2) what is the diagnostic performance of implant migration at 24 months postoperatively to predict later aseptic loosening of these components; and (3) how does long-term stem survivorship compare between groups with high and low early migration? - Methods. We evaluated early axial stem migration in 158 cementless THAs using EBRA-FCA. The EBRA-FCA measurements were performed during the first week postoperatively (baseline measurement) and at regular followups of 3, 6, and 12 months postoperatively and annually thereafter. The mean duration of followup was 21 years (range, 18-24 years). The stems studied represented 45% (158 of 354) of the cementless THAs performed during that time, and cementless THAs represented 34% (354 of 1038) of the THA practice during that period. No patient enrolled in this study was lost to followup. Multivariate survivorship analysis using Cox's regression model was performed with an endpoint of aseptic loosening of the femoral component. Loosening was defined according to the criteria described by Engh et al. and assessed by two independent observers. Patients with a diagnosis of prosthetic joint infection were excluded. Receiver operating characteristic (ROC) curve analysis was used to evaluate diagnostic performance of axial stem migration 1, 2, 3, and 4 years postoperatively as a predictor of aseptic loosening. Survivorship of hips with high (≥ 2.7 mm) and low (< 2.7 mm) migration was compared using a competing-events analysis. Results. Femoral components that had aseptic loosening develop showed greater mean distal migration at 24 months postoperatively than did components that remained well fixed throughout the surveillance period (4.2 mm ± 3.1 mm vs 0.8 mm ± 0.9 mm; mean difference, 3.4 mm, 95% CI, 2.5-4.4; p ≤ 0.001). Distal migration at 24 months postoperatively was a strong risk factor for aseptic loosening (hazard ratio, 1.98; 95% CI, 1.51-2.57; p < 0.001). The associated overall diagnostic performance of 2-year distal migration for predicting aseptic loosening was good (area under the ROC curve, 0.86; 95% CI, 0.72-1.00; p < 0.001). Sensitivity of early migration measurement was high for the prediction of aseptic loosening during the first decade after surgery but decreased markedly thereafter. Stems with large amounts of early migration (≥ 2.7 mm) had lower 18-year survivorship than did stems with little early migration (29% [95% CI, 0%-62%] versus 95% [95% CI, 90%-100%] p < 0.001). Conclusions. Early migration, as measured by EBRA-FCA at 2 years postoperatively, has good diagnostic capabilities for detection of uncemented femoral components at risk for aseptic loosening during the first and early second decades after surgery. However, there was no relationship between early migration patterns and aseptic loosening during the late second and third decades. EBRA-FCA can be used as a research tool to evaluate new cementless stems or in clinical practice to evaluate migration patterns in patients with painful femoral components. Level of Evidence. Level III, diagnostic study.